Perspectivas de mulheres que denunciam o vivido da violência: cuidado de enfermagem à luz de Schutz - Vieira, Letícia Becker (2011)
The research aimed to understand the reasons for the woman who performs the action to denounce his living in violent situations.It was developed a qualitative research with phenomenological approach, with theoretical framework of Alfred Schütz. The setting was the Police Station for Women and the Emergency Care Station in an inner city of Rio Grande do Sul/Brazil. The participants of the study were women aged from 18 to 59 years looking for the service to carry the record of violence by their partners. For production data, it was used a phenomenological interview, which ended at the 13th empathetic meeting, when it was realized the sufficiency of meanings. From their intentions it was revealed that women, when living deeply the action to denounce, expect to end the violence situation that they don t accept and don t tolerate anymore. They want to have peace and to be able to resume their plans and their life, with intent to separate from the companion. They have expectations about the need for justice and protection for themselves and their child (s). By revealing their motivation in denouncing, the woman establishes a relationship of anonymity with her partner, since the complaint goes through the decision to break with traditions that she no longer accepts and that cause her grief. From their daily experiences of violence, they began to question the common sense of knowledge, which typifies cultural patterns of social groups and takes an attitude of breaking with the typical formula of perceiving women in the relationship with the partner in the natural attitude. It was disclosed that, in the intersubjective relationship with the partner, there is lack of exchanges of views, claiming that this one hurts her rights as a person. Backed by legislation that prohibits violence, women begin to question such a situation, no more accepting it as a premise and they express the desire to don t share anymore a story that was being built in common. The expectations regarding the action to denounce express the desire to drive it until the end, as well the need to believe in justice and its outcome. The intention of the complaint reveals the need to protect and create their child (s) free (s) of violence assisted by them and sometimes experienced. They reveal their anguish in being alive to be able to take care of the child, once the partner threatens to take their life. Thus, the typical action, as vision for nursing, expands the understanding of the health professional, who can better direct their health care, from the subjectivity of the subjects. It is seen that nursing care should / could be facing the prospects of the women, be directed to women in situations of violence, from their social reality, embedded in their world, considering establishing relationships, life history, to recognize their needs and demands in health, from a dialogical perspective, aiming to break the cycle of naturalization and acceptance of violence.